COMMENTARY ON THE SECOND GENEVA CONVENTION Convention (II) for the Amelioration of the Condition of Wounded, Sick, and Shipwrecked Members of Armed Forces at Sea - Dörmann, Knut; Lijnzaad, Liesbeth; Sassòli, Marco; Spoerri, Philip 1963- (Cambridge University Press, 2017)
The application and interpretation of the four Geneva Conventions of 1949 have developed significantly in the sixty years since the International Committee of the Red Cross (ICRC) first published its Commentaries on these important humanitarian treaties. To promote a better understanding of, and respect for, this body of law, the ICRC commissioned a comprehensive update of its original Commentaries, of which this is the second volume. Its preparation was coordinated by Jean-Marie Henckaerts, ICRC legal adviser and head of the project to update the Commentaries. The Second Convention is a key text of international humanitarian law. It contains the essential rules on the protection of the wounded, sick and shipwrecked at sea, those assigned to their care, and the vessels used for their treatment and evacuation. This article-by-article Commentary takes into account developments in the law and practice to provide up-to-date interpretations of the Convention. The new Commentary has been reviewed by humanitarian-law practitioners and academics from around the world, including naval experts. It is an essential tool for anyone working or studying within this field